Impact of chronic idiopathic urticaria on patients’ quality of life in Jeddah, Saudi Arabia - Andijani, Fedaa S. (International Journal of Research in Dermatology, 2021)
Background: Urticaria is a common chronic dermatological disease that has a negative impact on the psychological status and the social interaction of the patients’ quality of life. The dermatology life quality index (DLQI) is one of the dermatology-specific instruments to evaluate the extent of the quality of life (QoL) impairment in the patients with skin diseases and provide an additional evaluation for the overall effectiveness of the treatment. Methods: This study was designed as a descriptive cross-sectional which was conducted in Jeddah city. Questionnaires with verified Arabic version of the DLQI were distributed and collected to the patients by dermatologists. Results: A total 79 patients were enrolled in the study. Male patients represented 48.1%, while female represented 51.9% and sex ratio was 1:1.1. The mean DLQI score in all patients was 10.67±5.54. 51.9% of the patients unfortunately with score of 11-20 had very large effect on their life. Conclusions: Chronic idiopathic urticaria (CIU) has a significant negative impact on the quality of life. In Saudi Arabia, few studies only have been done to evaluate the impact of CIU on patients’ life and more studies are needed to help the patient to improve the management’s strategy and the patients’ life.